Classification of prostate histological images using Vision Transformers: an analysis with stain normalization and ensemble learning - Albuquerque, Betânia Caroline Silva de; Castro, Hanna Beatriz Couto Monteiro Fernandes de; Neves, Leandro Alves; Nascimento, Marcelo Zanchetta do; Tosta, Thaína Aparecida Azevedo (Anais Estendidos da Conference on Graphics, Patterns and Images (SIBGRAPI); 2025: Anais Estendidos da XXXVIII Conference on Graphics, Patterns and Images, 2025)
Prostate cancer is the second most common cancer in men worldwide, diagnosed via histopathological evaluation of H&E-stained images. Gleason grading, however, is subjective and prone to inter-observer variability. Deep learning-based computer-aided diagnosis systems offer promising support, but stain color variations pose a challenge, motivating normalization algorithms. This study evaluates color normalization on H&E prostate cancer image classification using a pre-trained ViT and eight classifiers, including a majority voting ensemble. Binary classification on a public dataset compared benign and malignant cases across two normalization methods (SW-CCN and BKSVD) and original images. Results showed original images yielded superior ViT and classifier performance, despite more malignant cases being misclassified as benign. SVM with ViT feature extraction achieved the best overall performance, surpassing both the ensemble and ViT classifier.